2011
DOI: 10.1002/tal.571
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two horizontal components of earthquake on nonlinear response of torsionally coupled base isolated structures

Abstract: SUMMARY Torsion in base‐isolated structures using bilinear rubber isolators effected by two horizontal components of earthquake simultaneously is investigated under various principal parameters including number of storeys; ratio of uncoupled torsional frequency to lateral frequency in the superstructure; ratio of uncoupled torsional frequency to lateral frequency in the isolation system; mass eccentricity in the superstructure and isolation system; and, in addition, the direction of eccentricity. Structure was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In contrast to 2D simulations, structures analyzed in 3D can be subjected simultaneously to two orthogonal ground motion components, which is a more realistic way of representing actual seismic events in structural analyses. In the scientific literature, there are a number of studies that consider the coupling in both orthogonal horizontal directions subject to bidirectional excitations . Relevant analyses showed that the maximum horizontal displacement of a seismic isolator subjected to coupled bidirectional ground motion analyses can be higher compared with the uncoupled ones .…”
Section: Bidirectional Response Of Base‐isolated Structuresmentioning
confidence: 99%
“…In contrast to 2D simulations, structures analyzed in 3D can be subjected simultaneously to two orthogonal ground motion components, which is a more realistic way of representing actual seismic events in structural analyses. In the scientific literature, there are a number of studies that consider the coupling in both orthogonal horizontal directions subject to bidirectional excitations . Relevant analyses showed that the maximum horizontal displacement of a seismic isolator subjected to coupled bidirectional ground motion analyses can be higher compared with the uncoupled ones .…”
Section: Bidirectional Response Of Base‐isolated Structuresmentioning
confidence: 99%
“…In order to exert eccentricity in base isolation system (e b ), CM of base slab has been shifted with respect to CS of base isolation system. In parametric study, Ω tb is supposed to be one in all the models because of less effect of Ω tb on parameters such as the base displacement and the base shear (Khoshnoudian and Imani Azad 2011;Panchal and Jangid 2012) and uncoupled frequencies of base isolation system are calculated using the following equations:…”
Section: Base Isolation Systemmentioning
confidence: 99%
“…Khoshnoudian & Azizi and Khoshnoudian & ImaniAzad (Khoshnoudian and Azizi 2007;Khoshnoudian and Imani Azad 2011) investigated the influence of various essential parameters on the seismic torsional behavior of base-isolated structures mounted on elastomeric bearings. It was noted that the superstructure in the torsionally coupled base-isolated structure doesn't behave as a rigid body which is a common assumption in the isolated structure design.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are different methods for the design of tall buildings subjected to extreme loadings (e.g. earthquake attack), which includes base-isolation methods (Khoshnoudian and Azad, 2011;Mehrparvar and Khoshnoudian, 2011;Yamamoto et al, 2011); installation of semi-active dampers (Ribakov, 2011a(Ribakov, , 2011b, active dampers (Ribakov and Agranovich, 2011a), passive dampers (Chung et al, 2009;Lee et al, 2009;Ribakov and Agranovich, 2011b) and tuned mass dampers (Heo et al, 2009;Marano and Greco, 2009;Mohebbi and Joghataie, 2012) and by reinforcement details such that a plastic hinge region can be formed to dissipate energy through inelastic deformation without structural collapse (Pam and Ho, 2009;Yan and Au, 2010). Amongst these measures, the last method is generally applicable to medium-rise and tall buildings for performance-based design approach (Sabol and Nishi, 2011), while the former methods are only cost-effectively for very tall buildings.…”
Section: Introductionmentioning
confidence: 99%